Genomic, Morphological and Functional Characterization of Virulent Bacteriophage IME-JL8 Targeting Citrobacter freundii - Jia, Kaixiang; Yang, Nuo; Zhang, Xiuwen; Cai, Ruopeng; Zhang, Yang; Tian, Jiaxin; Raza, Sayed Haidar Abbas; Kang, Yuanhuan; Qian, Aidong; Li, Ying; Sun, Wuwen; Shen, Jinyu; et al. (Frontiers in Microbiology, 2020)
Citrobacter freundii refers to a fish pathogen extensively reported to be able to cause injury and high mortality. Phage therapy is considered a process to alternatively control bacterial infections and contaminations. In the present study, the isolation of a virulent bacteriophage IME-JL8 isolated from sewage was presented, and such bacteriophage was characterized to be able to infect Citrobacter freundii specifically. Phage IME-JL8 has been classified as the member of the Siphoviridae family, which exhibits the latent period of 30-40 min. Besides, according to pH and thermal stability of phage IME-JL8, it was demonstrated that this bacteriophage achieved a pH range of 4-10 as well as a temperature range of 4℃, 25℃ and 37 ℃. As revealed from the results of whole genomic sequence analysis, IME-JL8 covers a double-stranded genome of 49,838 bp (exhibiting 47.96% G+C content), with 80 putative coding sequences contained. No bacterial virulence- or lysogenesis-related ORF was identified in the IME-JL8 genome, so it could be applicable to phage therapy. As indicated by the in vitro experiments, phage IME-JL8 is capable of effectively removing bacteria (marking a decrease by 4.2 log units at 10 min), and biofilm can be formed in 24 h. According to the in vivo experiments, administrating IME-JL8 (1×107 PFU) was demonstrated to effectively protect the fish exhibiting a double median lethal dose (2×109 CFU/carp). Moreover, the phage treatment led to the decline of pro-inflammatory cytokines in carp with lethal infections. IME-JL8 was reported to induce efficient lysis of Citrobacter freundii both in vitro and in vivo, thereby demonstrating its potential as an alternative treatment strategy for infections attributed to Citrobacter freundii.